JOBL : A JOB LISTING WEBSITE - HAMDAN, MOHAMAD SYAZMEE (IRC, 2020)
This report gives a brief explanation of what I do for my Final Year Project 1 (FYP1) and Final Year Project 2 (FYP2). My project is developing a job listing website called JobL. This project background of study is about online job recruitment. The problem that I identify are low employment rate due to Covid-19, most of the online job website online did not offer job forshort period job and trust issue in hiring people through online job platform. The objective of my project is to conduct research on unemployment in Malaysia, to develop a job listing website for people to find short period job and to add a rating feature to the website. My scope of study is focusing on online job portals for example JobStreet, LinkedIn and MauKerja. The research method that I had been used for this project are self-learning and questionnaire survey. For the development methodology, I am using waterfall model to develop the website. What I can conclude from this project is we need to be aware and tackle the unemployment rate in Malaysia before things can get worse.